Aspects of population biology and behaviour of mobulid rays - Carpenter, Michelle (Department of Biological Sciences, 2024)
Manta and devil rays (Mobula spp.) are charismatic yet threatened species that remain poorly understood. The Inhambane Province in Mozambique is known to be home to the largest populations of manta rays in Africa, including the reef manta ray (M. alfredi) and the oceanic manta ray (M. birostris). However, research on other mobulid species, and in the region south of Tofo, including Závora in Mozambique and South Africa, has been limited. This thesis identifies critical sites and describes their characteristics, including habitat use, population abundance, and behaviour, for three species of mobulids: M. alfredi, M. birostris, and the shortfin devil ray, M. kuhlii. Chapter 1 comprises a literature review on the status and knowledge on mobulids in a global context, and within the southern African region, with focus on M. alfredi and M. birostris, due to the increased amount of information available on these species. Chapter 2 provides detailed information on the methodologies used throughout the thesis, some of which overlap. Chapter 3 utilises an 11-year photographic mark-recapture dataset spanning from 2010-2021 to investigate the size and structure of the M. alfredi population that aggregate at 'Red Sands' (RS), a reef cleaning station located at Závora, Mozambique. A total of 583 individual M. alfredi were identified using photographic mark recapture (photo-ID) of the unique ventral spot patterning. Pollock's Robust Design models were used to estimate annual abundances, emigration, annual apparent survival, and capture probability at RS during peak season, July-November, between 2016-2021. The resulting abundance estimates varied each year, with a range of 35 individuals (95% CI 30-45) up to 233 individuals (95% CI 224-249). Lagged Identification Rates were additionally used to describe the residency patterns of M. alfredi at Red Sands, revealing that despite site affinity to RS, individuals were overall transient within a given season, with an average residency of four days. Chapter 4 applies the methods used in Chapter 3 to report on South Africa's first photo-ID dataset for manta rays, including both M. alfredi and M. birostris, spanning from 2020-2022. Through the use of citizen science photographic donations and opportunistic snorkelling and diving, were used to document manta ray aggregation sites in the KwaZulu-Natal (KZN) Province. These same data were used to further document connectivity of M. alfredi between Mozambique and South Africa, revealing that at least 20% of all photographed individuals in South Africa had made international migrations to or from Mozambique. The distances travelled ranged from 435 km and 1,000 km, between the Aliwal Shoal Marine Protected Area (MPA), KZN and Závora, the second longest known migration for this species. Additionally, previously undocumented aggregations were found, including M. alfredi at the iSimangaliso Wetland Park and possibly M. birostris at Ballito. Aggregations in KZN were primarily related to surface feeding, with cleaning and courtship behaviours also documented. Chapter 5 analyses a 41-year catch dataset (1981-2021) provided by the KZN Sharks Board bather protection programme to investigate broad spatial-temporal trends in catch for manta rays (M. alfredi, M. birostris). Using Generalised Additive Models and the probability of encounter, the effects of annual and seasonal factors, moon phase, and location on catch rates are assessed. The size composition and demographics of the caught manta rays and the catch per unit effort at different beaches are also examined. The results revealed a significant decline in overall catches around 2000 (p<0.0001). Catches increased in summer, indicating seasonal visitation to South African waters. Moon phase had an effect on manta ray presence, with more catches during new and full moon phases. Over half of the catches included juveniles, whereby a total of 841 individuals (52% of total catch) of confirmed juvenile size class (1400-2500 mm disc width) were caught, particularly in the southernmost sampled area, from Hibberdene in the north to Mzamba in the south. Chapter 6 investigates a previously undocumented aggregation of M. kuhlii in the Aliwal Shoal MPA, and their cleaning behaviour by the bluestreak cleaner wrasse, Labroides dimidiatus. The study documented M. kuhlii sightings, behaviours, and associated environmental conditions during recreational snorkelling/diving. Generalised additive models (GAMs) were used to assess predictors of M. kuhlii presence and cleaning behaviour duration. The results showed that M. kuhlii were present in 56% of the survey days, with up to 150 individuals observed. The study recorded a total of 4.04 hours of M. kuhlii cleaning behaviour which was processed using frame by frame analysis. Sea surface temperature was found to be a significant predictor for M. kuhlii presence, while the absence of current and estimated horizontal visibility were significant predictors for longer cleaning durations. During recreational diving in the Aliwal Shoal MPA, first-time observations of M. kuhlii courtship were unexpectedly encountered and videoed in November 2020 and January 2021, which are detailed in Chapter 7. The common behaviours associated with mobulid courtship were documented: multiple males following a single female, rapid speed bursts, avoidance of the female, and swerving, which confirmed that M. kuhlii mating occurs in KZN waters. The collective results are concluded in Chapter 8, which indicate that both Závora and KZN waters provide important seasonal habitat for mobulid species along the southern African coastline. The findings of this work support other studies that show manta rays to use an expansive area, with seasonal affinities to certain locations, and transience during periods when conditions are not favourable for visitation. This demonstrates the importance of understanding site use within the larger home range of a given mobulid population. Therefore, this thesis has filled critical knowledge gaps and improved the overall understanding of mobulids in southern Africa, providing valuable information for conservation management efforts.